Reducing Mn Levels from Bore Well Water in Tembung Village by Filtration of Tea Bag Activated Carbon, Zeolite, Silica Sand and Gravel - Jumiati, Ety; Nasution, Nazaruddin; Prananda, Dika (BULETIN FISIKA; Vol 24 No 2 (2023): BULETIN FISIKA August Edition, 2023)
Research has been carried out to reduce Mn levels in Tembung village bore wells by filtering with tea waste activated carbon, zeolite, silica sand and gravel, to find out how the quality of bore well water after filtering using activated carbon from tea dregs, silica sand zeolite, and gravel. The composition variations of tea dregs activated carbon, zeolite, silica sand and gravel used are (A) 20 cm activated carbon: 15 cm zeolite: 15 cm silica sand: 10 cm gravel, (B) 15 cm zeolite: 15 cm silica sand: 10 cm gravel: 20 cm activated carbon, (C) 15 cm silica sand: 10 cm gravel: 20 cm activated carbon: 15 cm zeolite, and (D) 10 cm gravel: 20 cm activated carbon: zeolite 15 cm: 15 cm silica sand. The results of testing of bore well water after filtering with activated carbon tea, zeolite, silica sand and gravel with variations in the composition of samples A, B, C and D have met the clean water quality standard based on PERMENKES RI No. 32 of 2017. Based on the four variations in the composition of the filter material, the optimum variation in the raw material mixing composition was obtained with the variation in the composition of sample C with Mn content of 0.011 mg/L.